Dynamic capabilities for open innovation: A typology of pathways toward aligning resources, strategies and capabilities - Priyono, Anjar; Hidayat, Anas (Journal of open innovation, 2022)
The purpose of this study is to analyze how dynamic capabilities are integrated into open innovation to support firms pursuing innovation. Dynamic capabilities enable firms to adjust to emerging changes through redesigning resource configuration. Nevertheless, how dynamic capabilities are integrated into open innovation for obtaining external knowledge and resources has not been observed in previous studies. Utilizing seven small and medium enterprises (SMEs) with various degrees of knowledge and technology intensity as subjects, this qualitative study identified a typology of pathways for integrating dynamic capabilities into open innovation. This study found that firms' internal resources coupled with complementary assets obtained from open innovation determine what strategies to deploy and what capabilities are needed to execute the strategies. The fit among firms' resources, strategies, capabilities and emerging business environment is not serendipitous, but rather it must be designed and supported by collective efforts from participants across organizations. In other words, the nature of knowledge and degree of technology adoption determine how sensing, seizing and performing are applied in each phase of open innovation. The main drawback of qualitative study is that it cannot cover a large number of subjects, although it can scrutinize an abundant number of detailed data. Future research can analyze the findings of this study using a survey method covering a large number of firms from various industries so that generalizability can be assured.